Abrupt Change in Atmospheric CO2 During the Last Ice Age - Ahn, Jinho; Brook, Edward J. (IEDA: US Antarctic Program Data Center, 2013)
During the last glacial period atmospheric carbon dioxide and temperature in Antarctica varied in a similar fashion on millennial time scales, but previous work indicates that these changes were gradual. In a detailed analysis of one event, we now find that approximately half of the CO2 increase that occurred during the 1500 year cold period between Dansgaard-Oeschger (DO) Events 8 and 9 happened rapidly, over less than two centuries. This rise in CO2 was synchronous with, or slightly later than, a rapid increase of Antarctic temperature inferred from stable isotopes.